Meaning of Thrifting in the #TukarBaju Campaign in the Zero Waste Indonesia Community - Yunitasyia Nafa Zahro; Holy Rafika Dhona (LONTAR: Jurnal Ilmu Komunikasi, 2023)
The phenomenon of thrifting or buying used clothes is becoming increasingly popular among young people and has attracted public attention because it is considered as one of the sustainable efforts by applying the principles of sustainable fashion.In interpreting this, the researcher then chose the Tukar Baju community as the object of research as well as a representation of environmental activists engaged in the realm of sustainable fashion. This research uses a qualitative method with an ethnographic type of research to see the meaning of thrifting from Tukar Baju activists and how the process of interaction and exchange of meaning between individuals can strengthen the meaning of thrifting as a form of sustainable fashion effort. Researchers found a pyramid concept of "Buyerarchy of need" in interpreting thrifting as a continuous effort and thrifting is at level 4 and which means thrifting is not the only one. So, to strive for sustainable fashion through thrifting, people need to be smart and not impulsive consumers.